The productivity growth of Malaysian microfinance institutions: Implications for consumer, sustainable business and economic growth - Abdamia, Noranita; Fahmy-Abdullah, Mohd; Sieng, Lai Wei (Asian Economic and Financial Review, 2025)
Microfinance Institutions [MFIs] from 2009 to 2020, exploring implications for consumers, sustainable business, and economic growth. The Data Envelopment Analysis-Malmquist Productivity Index (DEA-MPI) is used to evaluate productivity growth, which incorporates three total inputs: branches, total staff, and total subsidies, and a single output: the total number of borrowers. The mean total factor productivity regression among Malaysian MFIs was 8.3%, primarily attributable to a technological regression of 13.4%. Technical efficiency improved modestly by 5.9%, with notable scale efficiency gains observed in 2010, remaining essentially stable thereafter. Pure technical efficiency is indicated by the lack of notable increases, underscoring managerial stagnation. Malaysian MFIs must strategically enhance their technological capabilities, despite stable scale efficiency and productivity declines, largely resulting from inadequate adoption of new technology and a lack of innovation. By providing incentives, training courses, and strategic alliances, policymakers should prioritize technological innovation and digital transformation. These measures will optimize MFI operations, improve service delivery to underserved markets, and align MFIs with Malaysia’s broader socioeconomic development objectives.